Alimentação de Macrobrachium rosenbergii (De Man, 1879)(crustacea, palaemonidae) durante a fase larval: efeitos da densidade de náuplios de Artemia, do tamanho das partículas de ração, do tipo de alimento e do fotoperíodo - Barros, Helenice Pereira de [UNESP] (2001)
The functional response (relationship between ingestion rate and food concentration) was determined for each larval stage of Macrobrachium rosenbergii. Artemia nauplii were supplied at six different densities: 2, 4, 6, 8, 10 and 12 ind/mL. The nauplii were counted manually using a Pasteur pipette and placed in Petri dishes containing 40 mL of brackish water (12‰). A single Macrobrachium rosenbergii larvae was placed in each Petri dish and after 24 hours the leftover nauplii were counted. Daily average ingestion rate by larva was calculated for each zoeal stage. Consumption pattern was defined by the model I = Im(1-e-kP). Ingestion rate increased with food density in the medium. The best relationship between predator and prey seemed to occur during stages IV and V. The high values for maximum ingestion (Im) and the low values for constant k obtained in the last larval stages indicate the necessity of supplementary diet during the final stages of development